A real-world study on clinical features and prognosis of Chinese breast cancer patients with brain metastases - Chen, Hong-dan; Liao, Xiao-wen; Chen, Xiao-geng; Su, Yu-nan; Pan, Ding-long; Chen, Guo-zhong; Wu, Min; Cai, Shuang-long (Frontiers in Oncology, 2026)
BackgroundThis study aimed to analyze the clinical characteristics and prognosis of breast cancer (BC) patients with brain metastases (BM).MethodsWe performed a retrospective analysis of breast cancer patients with brain metastases (BCBM) in a real-world setting.ResultsIn a cohort of 249 breast cancer brain metastasis (BCBM) patients (all female; median age 46 years), molecular subtypes were distributed as follows: luminal (38.95%), HER2-positive (32.93%), and triple-negative (28.11%). Distinct metastatic patterns were observed: luminal subtype correlated with bone metastases (55.73%, p<0.001), HER2-positive with liver metastases (46.34%, p<0.001), and luminal with leptomeningeal metastases (19.59%, p=0.002). For CNS-directed treatment, 70.28% received radiotherapy (69.71% whole-brain radiotherapy, 30.28% stereotactic radiosurgery), while 23.69% received no local treatment. After median follow-up of 63.1 months, 81.52% had died. Multivariable analysis identified HER2-positive subtype and brain metastasis as first metastatic site as protective for overall survival after brain metastasis (OS-BM), while leptomeningeal metastasis were independent risk factors.ConclusionThis study reveals distinct patterns of metastatic spread across breast cancer molecular subtypes and identifies key prognostic factors for survival after brain metastasis. The findings underscore the critical influence of tumor biology on disease progression and outcomes, highlighting the need for subtype-specific management strategies in BCBM patients.